El uso de la evidencia en las políticas públicas: el caso de las Evaluaciones de Desempeño y Ejecución Presupuestal en el sector Educación en el Perú - Navarro, Alejandra (2018)
This article aims to approach the use of evidence in the formulation of public policies. To this end, we analyze the independent evaluations of the Education sector, particularly the Performance Evaluations and Budget Execution (EDEP – for its acronym in Spanish), which we take as a case study. In order to present the context in which this tool is located, first a brief account of the literature is presented about the use of evidence in public policies and the relationship between knowledge and public policies in Peru. . Secondly, the analysis of five EDEPs of the Education sector is presented in the light of the following axes of analysis: i) the profile of the researchers and the methodology used in the research, and ii) the analysis of the fulfillment of the consigned commitments. The article concludes that EDEPs generate an intermediate degree in compliance with their recommendations, which is mediated, among other factors, by the type of public intervention evaluated; and questions the usefulness of the EDEP as an effective mechanism for evaluating and improving the design or component of a program, identifying opportunities to improve the tool, such as the methodological redesign, the simplification in the reporting of results, the empowerment of the matrix and its mechanisms, among others.